LC-MS/MS and NMR Studies for Identification and Characterization of Forced Degradation Products of Acalabrutinib - Mishra, Shweta; Chauhan, Ashlesha (Indian Journal of Pharmaceutical Education and Research, 2023)
A new method named "Stability Indicating LC-MS/MS" was developed to make analysis on acalabrutinib and this method was stable for this anticancer drug. In acid, basic and oxidation the drug was shown instability on these stress conditions. Acalabrutinib was used to form four degradation products and the developed method was used to separate based on “Zorbax C18 column (150 mm x 4.6 mm, 5 µm)" and for this separation the technique isocratic elution was used with the flow rate of 1.0 mL/min. It was found that the new developed method was valid as per the guidelines of ICH. A pathway known as fragmentation of drug was founded initially to identify the formed degradation products and in this identification LC-MS/MS method was used and also fragmentation studies were used. After the identification, isolation of the degradation products was done and (1H-NMR) was subjective for this process. The environment of basic, acid and oxidative were used to obtain the degradation products and these were isolated by the advanced techniques known as acid degradation product (DP1) of acalabrutinib with a molecular mass of 390.200 Da, empirical formula C21H19N5O3 with name as (S)-4-(8-amino-3-(1-(but-2-ynoyl)pyrrolidin-2-yl)imidazo[1,5-a]pyrazin-1-yl) benzoic acid". 442.100 Da is the molecular mass of base degradation product (DP2), C24H23N7O2 is the empirical formula with name as "(S)-4-(3-(1-acetylpyrrolidin-2-yl)-8-aminoimidazo[1,5-a]pyrazin-1-yl)-N-(pyridin-2-yl)benzamide". 498.400 Da is the molecular mass of another acalabrutinib base degradation product (DP3), C27H27N7O3 is the empirical formula which is known as "(S)-4-(8-amino-3-(1-(3-methoxybut-2-enoyl)pyrrolidin-2-yl)imidazo[1,5-a]pyrazin-1-yl)-N-(pyridin-2-yl)benzamide". 482.200 Da is the molecular mass of oxidation degradation product (DP4), C26H23N7O3 is the empirical formula which is known as "2-(4-(8-amino-3-(1-(but-2-ynoyl)pyrrolidin-2-yl)imidazo[1,5-a]pyrazin-1-yl)benzamido) pyridine-1-oxide".
Keywords: Acalabrutinib; Isolation; Characterization; Forced Degradation Studies; LC-MS/MS; NMR